Aktivitas Antibakteri Ekstrak Etanol Daun Ketapang (Terminalia Catappa L) Terhadap Bakteri Streptococcus Mutans - Asnan Nugroho; Sholikhah Deti Andasari (CERATA Jurnal Ilmu Farmasi, 2019)
Ketapang leaf (Terminalia catappa L) was a plant that has many benefits, one of which was antibacterial because it has active compounds such as alkaloids, flavonoids and tannins. The aimed of this study was to determine the effectiveness of the ethanol extract of ketapang leaf (Terminalia catappa L) as an antibacterial against Streptococcus mutans. This study used an experimental method, ketapang leaves as much as 500 grams macerated with ethanol 96% solvent for 5 days resulted in a yield of 8.68%. The ethanol extract of leaves obtained was tested for antibacterial effectiveness against Streptococcus mutans bacteria with variations in concentrations of 25%, 50%, and 75% by diffusion method. Determination of the inhibition zone was done by measuring the diameter of the clear zone formed around the disc. The results showed that at concentrations of 25%, 50% and 75% respectively 4.48 mm, 7.88 mm and 9.70 mm. Whereas the inhibitory zones in negative and positive controls are 0 mm and 19.70 mm respectively. The results show that the greater the concentration of extract the greater the inhibition zone formed. So, ethanol extract of ketapang leaves effectively inhibits the growth of Streptococcus mutans.